Cumulative Corticosteroid Dose Over Fifty‐Two Weeks in Patients With Systemic Lupus Erythematosus: Pooled Analyses From the Phase III Belimumab Trials. Issue 9 (September 2016) - van Vollenhoven, Ronald F.; Petri, Michelle; Wallace, Daniel J.; Roth, David A.; Molta, Charles T.; Hammer, Anne E.; Tang, Yongqiang; Thompson, April
Abstract : Objective: To examine the effects of treatment with belimumab on corticosteroid dose in patients with systemic lupus erythematosus (SLE) over 52 weeks in 2 randomized, controlled trials. Methods: Data on patients who were taking corticosteroids at baseline in the Study of Belimumab in Subjects with SLE trials were pooled post hoc to compare patients who received belimumab 10 mg/kg plus standard therapy with those who received placebo plus standard therapy. The primary end point was cumulative change from baseline in corticosteroid dose (prednisone equivalent) through week 52. Further analyses specifically examined oral corticosteroid dose. Results: At baseline, 966 of 1, 125 patients (86%) were receiving corticosteroids (478 belimumab 10 mg/kg and 488 placebo). Most were women (94%), their mean age was 37.1 years, mean Safety of Estrogens in Lupus Erythematosus National Assessment version of the SLE Disease Activity Index score was 9.8, and mean corticosteroid dosage was 12.5 mg/day. Over 52 weeks, there was a smaller increase in mean cumulative corticosteroid dose for the belimumab group than for the placebo group (531.2 mg versus 916.3 mg; P < 0.0001). Compared with placebo, the mean of all decreases in cumulative corticosteroid dose was higher with belimumab ( P = 0.0165), and the mean of all increases was lower ( P = 0.0005). More patients in the belimumab group had decreases in oral corticosteroid dose (38.5% versus 30.9%), and fewer had increases in dose (18.4% versus 30.7%), compared with placebo. Adverse events were comparable across groups. Conclusion: Our findings show a significantly smaller increase in cumulative corticosteroid dose over 1 year, more patients with decreases in oral corticosteroid dose, and fewer patients with increases in oral corticosteroid dose in the belimumab group compared with the placebo group. These data suggest that belimumab may be steroid sparing.